Sistema de costeo por actividad en la producción de camarones de agua dulce en la camaronera mano poderosa del cantón Chone - Chinga Barrera, Yaixza Yomayra (2019)
In the business world due to the globalized world companies are immersed in a high competitiveness, but to be more competitive they must control and harmonize their expenses and accounting records in a timely manner, in this area in the shrimp farm MANO PODEROSA has identified the lack of a tool that allows to determine the costs associated to each one of the activities in the management of freshwater shrimp production. For this reason, a cost-per-activity system is proposed that provides economic information on the costs generated in production for the easy understanding of the distribution of economic resources in each activity. For the realization of this work, scientific articles were used that are sources of theoretical knowledge and support of the present project, work that is focused on recognizing the importance of keeping a cost control for the company dedicated to the shrimp activity. It is necessary to complete that to carry out the present work the interview was used, which was directed to the owner of the shrimp farm, as well as direct observation of the activities involved in the production, to complete the investigation the descriptive research method was used, deductive, historical and accounting. To conclude, the proposed costing system is aimed at improving the records of costs involved in shrimp farming, thus providing a greater profit margin since it will be known which activities generate more costs, which require more investment and which will be a cost reduction.